Public Perception of Accessibility to Education, Health, Economy, and Living Eligibility in Tomohon City - Irfan Rifani,; Christian Beckham Liuw,; Ellen Eva Poli,; Muhamad Isa Ramadhan, (Technium Social Sciences Journal, 2023)
This study aims to determine public perceptions of the accessibility of education, health, economy, and the livability of people in Tomohon City. The research method used is quantitative descriptive. Data collection by questionnaire. The results showed that based on the results of the study showed ease of access and high-quality levels of education, health, economy, and livability but there are still low things or percentages that show bad numbers even on a small scale. The future thing that must be done by the government to follow up on several indicators that still need to be improved is to pay attention to improving the quality and quantity of education, health, economy, and livability.